Broadband absorption enhancement of monolayer graphene by prism coupling in the visible range - Heo, Hyungjun; Lee, Sangjun; Kim, Sangin (Carbon, 2019)
We experimentally demonstrated the broadband absorption enhancement of monolayer graphene embedded in the center of a dielectric cavity of the prism coupling configuration in the visible spectral range. The absorption peak is enhanced up to 86.1% at λ = 650 nm with a 3 dB bandwidth of 314 nm (from 542 nm to 856 nm). The absorption performance is the best experimental result for monolayer graphene in the visible range, to the best of knowledge. The improved absorption is attributed to enhanced light-graphene interaction via the cavity mode formed in the dielectric layer with the properly chosen graphene position. The proposed structure is suitable to a high-efficiency broadband photodetector based on monolayer graphene due to the simple fabrication process and the high fabrication tolerance.
Keywords: Absorption peaks; Absorption performance; Broadband absorption; Dielectric cavities; Dielectric layer; Fabrication process; Fabrication tolerances; Visible spectral range